(untitled) (Bangladesh Heart Journal, 2021)
Objective: Despite the evolution of interventional techniques and operator experience, percutaneous revascularization of complex coronary lesions especially calcified lesions remains challenging because of lower procedural success and higher restenosis rates. Limited data are available on the effect of rotational atherectomy (RA) plus stenting in the treatment of complex calcified lesions of coronary artery disease. This study was aimed to investigate the characteristics, short and long term outcomes in patients undergoing RA. Material and Methods: A database search was performed from the year 2008 to 2013 in National Heart institute, Malaysia. A total of 16009 patients who underwent PCIs were enrolled in 2 groups, RA group (258 patients) and non RA group (15751 patients). The Chi square test and Kaplan - Meier analysis were used. Results: Male patients (73.6%) and elderly population (63.2%) were predominant in this study.The RA group had more co-morbidities such as diabetic on insulin (34%) and chronic kidney disease (57%). The lesions in RA group were more complex with higher Type C lesion (68.8%) and longer lesion (20.6%) compared to non RA group. Despite higher patient risk profile, the success rate of revascularization remains high in RA group (99.3%) as in non RA group (97%) (p value 0.89%). More importantly there were no significant difference in in-hospital mortality, myocardial infarction and stent thrombosis in both group (p value 0.1). In 1 year Kaplan - Meier survival graph, there were better survival noted in non RA group (97.7%) compare to RA (89.6%) (p value <0.005), Conclusion: The use of RA allows debulking of a calcified lesion and possibly explains the higher acute procedural success rates. However, the lower 1-yearsurvival in the RA group highlights the higher associated baseline comorbitidity in this group. Therefore, besides coronary intervention, this RA group requires aggressive medical therapy through a multi-disciplinary approach. Bangladesh Heart Journal 2020; 35(2) : 140-146